THE INFLUENCE OF SOCIAL MEDIA AND THE FEAR OF MISSING OUT ON GENERATION Z PURCHASING DECISION - Borshalina, Tita; Tjahjar, Ariel Rama; Febrita, Khairunnisa Nur; Aulia, Rivalda; Putra, Seja Alfanny Adhimas; Zulmartiansyah, Mochammad Rahman (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to examine (1) the influence of social media on purchasing decisions, (2) the influence of Fear of Missing Out on purchasing decisions, and (3) the influence of social media and Fear of Missing Out on purchasing decisions. The method used in this research is quantitative method. The data was collected using a questionnaire instrument, which was then analyzed using multiple regressions with classical assumption tests. The sample in this study is Generation Z in Bandung. Results of this study showed that (1) social media had no significant influence on purchasing decisions, (2) Fear of Missing Out had a significant influence on purchasing decisions, and (3) social media and Fear of Missing Out had a significant influence on purchasing decisions. The result of simultaneous regression calculation obtained that the whole dimensions of the social media and FoMO variables had a significant influence on the purchasing decisions of Generation Z. Since social media has no significant effect on purchasing decisions in Generation Z, companies cancarry out other strategies such as word-of-mouth techniques, decoy effect, or e-mail marketing to improve purchasing decisions.